Active Cyclin A-CDK2 Complex, a Possible Critical Factor for Cell Proliferation in Human Primary Lung Carcinomas - Dobashi, Yoh (American Society for Investigative Pathology, 1998)
Expression of cyclins A and E and cyclin-dependent kinase 2 (CDK2) was examined immunohistochemically in 190 cases of human lung carcinoma. Cyclin A and CDK2 were expressed in the majority of squamous cell carcinomas, small cell carcinomas, and large cell carcinomas, but in significantly fewer cases of adenocarcinomas. Cyclin E was expressed in a minority of all subtypes. In particular, well differentiated cells in squamous cell carcinoma stained positively for cyclin E; in contrast, cyclin A was expressed in the nonkeratinized proliferating areas of the tumor nests. Immunoblotting revealed that all these proteins were expressed at higher levels in tumor tissues than in adjacent normal tissues. Immunoprecipitation also revealed higher levels of cyclin A and cyclin E associated with CDK2 in tumor tissues. Furthermore, tumor tissues which exhibited higher cyclin A and CDK2 expression also had higher CDK2 kinase activity. However, cyclin E-associated kinase activity was barely detectable even in tumor samples exhibiting higher cyclin E expression. Consistent with these data, elevated expression of cyclin A correlated to shorter survival periods in contrast to expression of cyclin E, which correlated to longer survival periods. These results suggest that in human lung carcinomas, elevated expression of active cyclin A-CDK2 complexes with associated higher CDK2 kinase activity is critical for promoting cell cycle progression and unrestrained proliferation of tumor cells and can be a predictive marker for patients’ prognosis. On the other hand, immunohistochemical detection of cyclin E-CDK2 reflects accumulation of inactive forms of protein complexes, implying differentiation or senescence of the tumor and the better prognosis.